Illusion of spirituality in the world of information completeness - Zuiev, Serhii (Actual Problems of Mind, 2017)
The article considers the phenomenon of information isolation as one of the main characteristics of modern civilization. The author proves the fundamental impossibility of transferring such concepts as spirituality, personality, freedom, etc., to the world of information from the world of knowledge and creativity, but the presence of these concepts is necessary for self-complacency and mental comfort of a person.